1994
DOI: 10.1046/j.1471-4159.1994.63010207.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory and Inhibitory Effects of A1 and A2A Adenosine Receptor Activation on the Electrically Evoked [3H]Acetylcholine Release from Different Areas of the Rat Hippocampus

Abstract: The modulation by adenosine analogues and endogenous adenosine of the electrically evoked release of [3H]acetylcholine ([3H]ACh) was compared in subslices of the three areas of the rat hippocampus (CA1, CA3, and dentate gyrus). The mixed A1/A2 agonist 2‐chloroadenosine (CADO; 2–10 µM) inhibited, in a concentration‐dependent manner, the release of [3H]ACh from the three hippocampal areas, being more potent in the CA1 and CA3 areas than in the dentate gyrus. The inhibitory effect of CADO (5 µM) on [3H]ACh releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 28 publications
10
90
0
Order By: Relevance
“…As illustrated in Fig. 2A, 2-chloroadenosine (10 AM) inhibited the evoked release of acetylcholine, in accordance with previous observations in hippocampal slices (Cunha et al, 1994a). This inhibitory effect was abolished by the adenosine A 1 receptor selective antagonist, DPCPX (20 nM), indicating that it is an adenosine A 1 receptor-mediated effect.…”
Section: Pharmacological Characterization Of Facilitatory Adenosine Asupporting
confidence: 91%
See 2 more Smart Citations
“…As illustrated in Fig. 2A, 2-chloroadenosine (10 AM) inhibited the evoked release of acetylcholine, in accordance with previous observations in hippocampal slices (Cunha et al, 1994a). This inhibitory effect was abolished by the adenosine A 1 receptor selective antagonist, DPCPX (20 nM), indicating that it is an adenosine A 1 receptor-mediated effect.…”
Section: Pharmacological Characterization Of Facilitatory Adenosine Asupporting
confidence: 91%
“…3 H]actylcholine in the total tritium outflow, [ 3 H]acetylcholine was separated using a cation exchanger, tetraphenylboron, after phosphorylation of [ 3 H]choline, as previously described (Cunha et al, 1994a).…”
Section: [ 3 H]acetylcholine Release From Nerve Terminalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ATP -activating P2X receptors located in the postsynaptic sites (Rubio & Soto, 2001) -takes part in the excitatory transmission and synaptic plasticity in CA1 (Pankratov et al, 1998(Pankratov et al, , 2002 and CA3 regions (Mori et al, 2001) and regulates the release of glutamate and GABA via P2X 7 receptors expressed on the presynaptic sites (Sperla´gh et al, 2002). Extraneuronal ATP is inactivated by the ectonucleotidase enzyme cascade which in turn gives rise to the formation of extracellular adenosine acting as a neuroprotective modulator, inhibiting neuronal discharge and modulating the release of various transmitters via A 1 and A 2A receptors respectively (Cunha et al, 1994;Cunha & Ribeiro, 2000;Cunha, 2001a;Masino et al, 2002). In line with this concept, the frequency-dependent contribution of ATP to extracellular adenosine levels (Cunha et al, 1996) and the rapid and highly effective in situ formation of adenosine from pressure-ejected ATP has been shown in earlier studies (Dunwiddie et al, 1997).…”
Section: Introductionmentioning
confidence: 58%
“…Other studies have reported that A1 and A2 A receptors are often expressed in the same regions [e.g., hippocampus (Cunha et al, 1994) and neuromuscular junction ] and indeed on the same nerve terminals at the neuromuscular junction . The coexistence of both subtypes of high-affinity adenosine receptors leads to the question of which receptor adenosine preferentially activates.…”
Section: Preferential Activation Of A1 or A2 A Receptors?mentioning
confidence: 92%